Inhibition of African Swine Fever Virus Replication by Porcine Type I and Type II Interferons - Fan, Wenhui; Jiao, Pengtao; Zhang, He; Chen, Teng; Zhou, Xintao; Qi, Yu; Sun, Lei; Shang, Yingli; Zhu, Hongfei; Hu, Rongliang; Liu, Wenjun; Li, Jing (Frontiers in Microbiology, 2020)
Interferons (IFNs) are proteins produced by a variety of cells during the process of virus infection. It can activate the transcription of multiple functional genes in cells, regulate the synergistic effect of multiple signaling pathways, and mediate a variety of biological functions such as antiviral activity and immune regulation. The symptoms of hosts infected with African swine fever virus (ASFV) depend on the combined interaction between viruses and the host. However, it is unclear whether IFNs can be used as an emergency preventive treatment for ASFV. This study focused on the use of recombinant porcine IFNs, produced by Escherichia coli, to inhibit the replication of ASFV. The activity of IFN against ASFV was detected using primary alveolar macrophages at different doses through immunofluorescence assays and quantitative real-time PCR. We found that both 1000 and 100 U/mL doses significantly inhibited the replication of ASFV. Meanwhile, we found that IFNs could significantly trigger the production of a variety of IFN-induced genes (IFIT1, IFITM3, Mx-1, OASL, ISG15, PKR, GBP1, Viperin, BST2, IRF-1 and CXCL10) and MHC molecules, which play key roles in resistance to virus infection. Peripheral blood samples were also obtained from surviving pigs treated with IFNs, and the viral load was determined. Consistent with in vitro tests, low-dose (105 U/kg) recombinant porcine IFNs (PoIFN-α and PoIFN-γ) significantly reduced viral load compared to that with high-dose (106 U/kg) treatment. Our results suggest that recombinant porcine IFNs have high antiviral activity against ASFV, providing a new strategy for the prevention of African swine fever.